2010
DOI: 10.1186/1477-7525-8-42
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of numerical and verbal rating scales to measure pain exacerbations in patients with chronic cancer pain

Abstract: BackgroundNumerical rating scales (NRS), and verbal rating scales (VRS) showed to be reliable and valid tools for subjective cancer pain measurement, but no one of them consistently proved to be superior to the other. Aim of the present study is to compare NRS and VRS performance in assessing breakthrough or episodic pain (BP-EP) exacerbations.MethodsIn a cross sectional multicentre study carried out on a sample of 240 advanced cancer patients with pain, background pain and BP-EP intensity in the last 24 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(107 citation statements)
references
References 38 publications
2
93
0
9
Order By: Relevance
“…However, the pain intensity at time of meaningful pain relief has never been assessed. In the measurement of cancer pain exacerbations, patients commonly use numerical rating scales more appropriately than verbal scales 7 . Numerical scales have been commonly used as a single entity, percentage pain intensity difference, the sum of pain intensity differences, pain relief, and percentage of maximum total pain relief.…”
Section: Introductionmentioning
confidence: 99%
“…However, the pain intensity at time of meaningful pain relief has never been assessed. In the measurement of cancer pain exacerbations, patients commonly use numerical rating scales more appropriately than verbal scales 7 . Numerical scales have been commonly used as a single entity, percentage pain intensity difference, the sum of pain intensity differences, pain relief, and percentage of maximum total pain relief.…”
Section: Introductionmentioning
confidence: 99%
“…However, in a systematic review of 54 studies comparing unidimensional scales, a nrs demonstrated better compliance in 15 of 19 studies comparing it with a vas and a vrs, and it was the recommended tool in 11 studies on the basis of higher compliance rates, better responsiveness and ease of use, and good applicability relative to a vas or vrs 28 . Brunelli et al 29 also demonstrated that, in cancer patients, a nrs was better than a vas in distinguishing between background pain and peak pain intensity, with a lower proportion of patients giving inconsistent evaluations (14% vs. 25%). In addition a nrs showed higher reproducibility in the measurement of pain exacerbation.…”
Section: Assessment Guides and Toolsmentioning
confidence: 99%
“…La variable de salida, magnitud del dolor se estimó utilizando la escala análoga del dolor; la primera versión de este instrumento fue introducida por Downie en 1978 10 , y ha sido satisfactoriamente evaluada en tiempo reciente, reflejando una alta capacidad discriminatoria para diferenciar el dolor subyacente de los picos de dolor y también una alta reproducibilidad (Kappa de Cohen 0,86), comparada con las escalas visuales del dolor 11 . Mediante este instrumento las pacientes clasifican la magnitud del dolor en valores numéricos que van de 0 a 10, siendo 0 la ausencia de dolor y 10 el máximo dolor imaginable.…”
Section: Materialses Y Métodosunclassified